PELATIHAN PENGGUNAAN THINGLINK, SEVEN TOOLS, CLUSTERING DATA MINING UNTUK GURU SMA - Fitriana, Rina; Habyba, Anik Nur; marie, Iveline anne; Kemala Sari, Debbie (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2025)
Community Service (PkM) entitled Training on the Use of Thinglink, Seven Tools, and Clustering Data Mining was conducted by lecturers, students, and laboratory staff from the Industrial Engineering Department, Faculty of Industrial Technology, Universitas Trisakti. The purpose of this PkM activity was to train and enhance the skills of teachers at SMAN 2 Tangerang Selatan in developing teaching materials using Thinglink and processing data utilizing the clustering method in data mining. The methods employed in this PkM included partner identification, proposal preparation, program socialization, implementation, and the preparation of reports and deliverables. This activity aimed to assist teachers in teaching and data grouping within the school environment. The activity was held on February 5–9, 2024, conducted online via Zoom and offline at SMAN 2 Tangerang Selatan. This PkM was carried out by lecturers and students of the Industrial Engineering Department, Faculty of Industrial Technology, Universitas Trisakti, and the Quality Engineering laboratory staff. The materials provided included the Seven Tools, Clustering Data Mining, and training on using Thinglink to develop teaching materials, followed by a question-and-answer session, discussion, and questionnaire completion. Teachers were also given assignments and allotted time to present their work. This Community Service activity will provide benefits, increase knowledge, and foster collaboration between both parties.  The output of this activity is a poster and a certificate for community service.